2019
DOI: 10.1111/ede.12278
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of cnidocyte development in the moon jellyfish Aurelia

Abstract: Stinging cells called cnidocytes are a defining trait of the cnidarians (sea anemones, corals, jellyfish, and their relatives). In hydrozoan cnidarians such as Hydra, cnidocytes develop from interstitial stem cells set aside in the ectoderm. It is less clear how cnidocytes develop outside the Hydrozoa, as other cnidarians appear to lack interstitial stem cells. We addressed this question by studying cnidogenesis in the moon jellyfish (Aurelia) through the visualization of minicollagen-a protein associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…1A). This suggested the presence of PMTs in studied proteins consistent with previous reports from cnidarians (Engel et al, 2001; Adamczyk et al, 2008; Gold et al, 2019). Our computational analyses of minicollagens performed to predict PMTs revealed that both proteins showed O-linked glycosylations and numerous hydroxylations (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…1A). This suggested the presence of PMTs in studied proteins consistent with previous reports from cnidarians (Engel et al, 2001; Adamczyk et al, 2008; Gold et al, 2019). Our computational analyses of minicollagens performed to predict PMTs revealed that both proteins showed O-linked glycosylations and numerous hydroxylations (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…The expression of other genes linked to nematogenesis, PaxA , Mef2 , and SoxB2 , 33 was also upregulated from AES to AE ( Figure 4 J). The expression of Ggt1 , Nematogalectin, and AurNcol-1 , which maintain nematocyst structure and discharge, 33 , 34 , 35 was considerably downregulated in AP but upregulated to different degrees from AES to AE, compared with that in the same stages of the control group ( Figure 4 J). Similarly, the expression of DKK3 , Nas4 , Nas8 , MACPF domain protein , and Toxin TX1 , encoding nematocyst venom proteins, 34 , 36 was downregulated in AP and elevated thereafter, compared with that in the same stage of the control treatment ( Figure 4 J).…”
Section: Resultsmentioning
confidence: 98%
“…First, nematocytes, which are capable of predation and defence, could be recognised by their co-expression of genes encoding multiple venoms and capsule proteins, such as minicollagen 19 , DKK3 18 and Collagen-like 18 (Figure 2b, d; Figure S2; Table S1). The proportion of nematocytes showed a steady increase from planula to medusa, indicating predation strategies of Aurelia changed during development (Figure 2c).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the composition of cell types captured by single-cell sequencing was comparable across 6 different life stages, and marked changes were observed in the proportions of cell types during development (Figure 2c). First, nematocytes, which are capable of predation and defence, could be recognised by their co-expression of genes encoding multiple venoms and capsule proteins, such as minicollagen 19 , DKK3 18 and Collagen-like 18 (Figure 2b, d; Figure S2; Table S1). The proportion of nematocytes showed a steady increase from planula to medusa, indicating predation strategies of Aurelia changed during development (Figure 2c).…”
Section: Atlas Of Aurelia Coerulea Cell Typesmentioning
confidence: 99%